KNOWLEDGE BASED ECONOMY: OPPORTUNITIES AND CHALLENGES - Milewska, Anna (Proceedings of the International Scientific Conference "Economic Sciences for Agribusiness and Rural Economy", 2018)
Nowadays, we can observe in different business and academicals environments an ongoing dialog about knowledge – based economy, due to the fact, that economies are increasingly based on knowledge and information. Practically it means, that companies have started looking for answers for plenty important questions – what ‘knowledge’ exactly means and what kind of knowledge is significant from business continuity perspective? What exactly is a driver of productivity and economic growth? Business executives have to face also other challenges: how all this knowledge has to be managed and how to adapt to swiftly changing circumstances? Should it be centralized in shared services centres forms or maybe outsourced based on business process outsourcing strategy? Do companies should establish cooperation with universities or R&D institutes based on the cluster structure? In this article the author will characterized the knowledge as a source of competitiveness, increasing importance of science and try to summarize best practices in that field.